2002
DOI: 10.1044/1092-4388(2002/056)
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem in Children With Specific Language Impairment

Abstract: The purpose of this preliminary study was to probe the self-perceptions of a group of children with specific language impairment (SLI) and their typically developing peers. A measure of self-esteem was administered to 46 children between the ages of 6 and 9 years old and 34 children between the ages 10 and 13. In the younger group, there were no statistically significant differences between children with SLI and typically developing children in the way they perceived themselves across domains of competence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
116
0
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(130 citation statements)
references
References 19 publications
5
116
0
9
Order By: Relevance
“…Other SLI studies have examined domain-specific self-esteem, thus complicating the picture. Studies of younger children (6 to 9 years) with SLI have not found evidence of lower domainspecific self-esteem in these children when compared to typically developing peers Self-esteem, shyness and sociability 24 (Jerome et al, 2002;Lindsay et al, 2002). On the other hand, Marton et al (2005) found that 7-to 10-year-olds did have lower social self-esteem scores (using a different scale) than age-matched peers.…”
Section: Global Self-esteem and Slimentioning
confidence: 90%
See 3 more Smart Citations
“…Other SLI studies have examined domain-specific self-esteem, thus complicating the picture. Studies of younger children (6 to 9 years) with SLI have not found evidence of lower domainspecific self-esteem in these children when compared to typically developing peers Self-esteem, shyness and sociability 24 (Jerome et al, 2002;Lindsay et al, 2002). On the other hand, Marton et al (2005) found that 7-to 10-year-olds did have lower social self-esteem scores (using a different scale) than age-matched peers.…”
Section: Global Self-esteem and Slimentioning
confidence: 90%
“…However, one study did find lower social Self-esteem, shyness and sociability 5 self-esteem in 7-to 10-year-olds with SLI (N = 19), when compared with agematched controls, and this difference was large (d = 0.9) (Marton, Abramoff, & Rosenzweig, 2005). Generally, older children with SLI (10-to13-year-olds) have been found to have significantly lower domain-specific self-esteem scores compared with typically developing peers, particularly in the academic and social domains (Jerome et al, 2002;Lindsay, Dockrell, Letchford, & Mackie, 2002). Jerome et al (2002) argued that young children with SLI may have adequate self-esteem because they are unaware of their academic and social failings.…”
Section: Self-esteemmentioning
confidence: 96%
See 2 more Smart Citations
“…There is evidence, however, that older children with SLI (10 to 13 years) have poorer perceived social acceptance compared to typically developing peers (Jerome et al, 2002;Lindsay, Dockrell, Letchford, & Mackie, 2002). Dockrell, Lindsay, Palikara and Cullen (2007) found that from 8 to 17 years of age, young people with SLI had Social stress 7 lower social self-perceptions compared to US norms using the Harter scales.…”
Section: Social Skills and Social Acceptancementioning
confidence: 99%